ANALISIS NILAI TUKAR NELAYAN PADA USAHA NELAYAN TRADISIONAL DI KELURAHAN TANDURUSA KECAMATAN AERTEMBAGA KOTA BITUNG - Rumopa, Sheren Dessy Natalia; Andaki, Jardie A.; Longdong, Florence V. (Universitas Sam Ratulangi, 2020)
AbstractThe purpose of this research is to determine the Exchange Rate of Traditional Fishermen with a hand line in Tandurusa Village, Aertembaga District.This research was carried out in Tandurusa Village, Aertembaga District, Bitung City, in August - December 2019.The method used in this research is survey. Data collected in this study consisted of primary data and secondary data. Primary data were obtained directly from traditional fisherman respondents by hand line and secondary data were obtained directly from the Tandurusa Kelurahan office. The analysis in this study used 2 (two) data analysis technique models. For clarity, the two models will be explained in the following sections. In this study, the intended income is gross income or can be called a fisherman's household income. Fishermen Exchange Rate (NTN) according to Sugiarto (2009).Based on the results and discussion of this study, it can be concluded: 1) the total income of traditional fishermen using hand line fishing gear cannot cover the subsistence needs (basic needs) of fishing families, with NTN of 0.90, while the income of fishermen can cover the costs of traditional capture fisheries business with NTN of 3.15; and 2) observations and calculations in September and October 2019 did not increase and decrease in NTN, with an NTN index (iNTN) of 100.Suggestions that can be submitted based on research, namely: 1) the need for NTN calculations for one year of observation because observations in one have complete data on the tides of fishing businesses that often experience good seasons and famine; and 2) traditional fishermen need to diversify their businesses (fishing work with nets, stalls, boat rental for tourism), which can help traditional fishermen cover subsistence needs.Keywords: traditional fishermen, subsistence, income, NTN